The Combustion Behavior of Eriobotrya japonica Stones - Sutcu, H.; Piskin, M. B. (TAYLOR & FRANCIS INC, 2013)
This article investigates the combustion characteristics and combustion kinetics of Eriobotrya japonica stones by thermogravimetric analysis. The combustion experiments were conducted at heating rates of 5 and 50 degrees C/min in the presence of oxygen. The reaction degree, the activation energy, and the exponential factor of the combustion process were calculated by employing the Coats and Redfern kinetic model.
Keywords: Coats and Redfern; combustion; heating rate; kinetics; thermogravimetric analysis; BIOMASS; FUEL; Energy & Fuels; Engineering; Environmental Sciences & Ecology